Infantile Library Miriam Álvarez Brenes: Interdisciplinary Perspective of the Given Workshops from 2000 to 2009 - Mora Valverde, María Marjorie (2016)
This article presents the main results of a study that analyzes the contributions of the children’s library to the people of the communities of University Gardens 1 and 2 of Heredia and other communities in the province, through educational workshops. These workshops have been characterized by the meaningful participation of students from different specialties, such as education and psychology, integrated into the work library science for the benefit of the user community. In the period from 2000 to 2009 were given a total of 90 workshops, 86 to children’s and four families in the community. Also, there were 11 talks, one on children and ten families. Workshops of the total received by children, the language has been taught in more and comprise 18,6%, followed by promotion of reading with 16,3% and Christmas themes with the same percentage and the school readiness12,8%, these issues comprise 64,4% of the workshops.